2020
DOI: 10.1016/j.beproc.2019.104022
|View full text |Cite
|
Sign up to set email alerts
|

Prairie vole offspring only prefer mothers over fathers when mothers are a unique resource, yet fathers are the primary source of variation in parental care

Abstract: In biparental species, each parent represents a semi-independent source of variable caregiving. The nature of care may differ between parents, and the type of care offspring seek is likely to change across development. We asked if caregiving differed between prairie vole (Microtus ochrogaster) mothers and fathers, and which parent pups prefer over development. We categorized parents as high-or low-contact based on daily recordings of grooming and brooding behavior. Pups were tested for their preferences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“… Thomas and Birney (1979) argued that male and female prairie voles contribute many of the same behaviors to offspring care. Other experiments have since shown that, compared to mothers, fathers tend to be more variable in their offspring care (e.g., Solomon, 1993 ; Finton and Ophir, 2020 ; Kelly et al, 2020 ). Consistent with all of this, we report sex differences in the patterns of adjustments in pup age-related behaviors, indicating that mothers and fathers exhibit differential sensitivities and responses to offspring developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“… Thomas and Birney (1979) argued that male and female prairie voles contribute many of the same behaviors to offspring care. Other experiments have since shown that, compared to mothers, fathers tend to be more variable in their offspring care (e.g., Solomon, 1993 ; Finton and Ophir, 2020 ; Kelly et al, 2020 ). Consistent with all of this, we report sex differences in the patterns of adjustments in pup age-related behaviors, indicating that mothers and fathers exhibit differential sensitivities and responses to offspring developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas and Birney (1979) argued that male and female prairie voles contribute many of the same behaviors to offspring care. Other experiments have since shown that, compared to mothers, fathers tend to be more variable in the degree to which they care for offspring (e.g., Solomon, 1993; Kelly et al 2020; Finton & Ophir 2020). Consistent with all of this, we report sex differences in the patterns of adjustments in pup age-related behaviors, indicating that mothers and fathers exhibit differential sensitivities and responses to offspring developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…When maternal behaviors were compared in the days following parturition, no group differences were found. Other studies have found that even though male prairie voles are active participants in caregiving, mothers consistently provide high levels of care to offspring, whereas caregiving across fathers varies widely (Kelly et al 2020; Finton & Ophir 2020; Solomon 1993). These findings reveal that variation in parental experience induced by the removal of the parenting partner has substantial context-specific behavioral and neuroendocrinological consequences for prairie vole mothers during the perinatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Prairie voles display a complex system of offspring care, including sole maternal care, biparental care, and occasionally additional alloparental care from philopatric nonreproductive offspring [Thomas and Birney, 1979;Getz et al, 1993]. Thomas and Birney [1979] demonstrated that fathers engage in all aspects of parental care except lactation; however, recent work has suggested that fathers might engage in caregiving behavior in disproportionate amounts or provide subtle but qualitatively different forms of care [Finton and Ophir, 2020;Rogers and Bales, 2020]. As a result, variable parental environments attributable to the total care from single or biparental caregiving, or more nuanced variation attributable to individual variation of one or more parents, create the opportunity for differential developmental factors to shape adolescent [Perkeybile et al, 2013] and adult [Rogers and Bales, 2020] phenotypes.…”
Section: Individual Level Effectsmentioning
confidence: 99%